Analysis of the UPTD Strategy for Community Health Centers with BLUD Status in Jember District Using the SPACE Matrix Approach - Heruddin, Heruddin; Suryaningsih, Ika Barokah; Dewanto, Iwan (Jurnal Kesehatan Komunitas, 2024)
The change of status of 50 Puskesmas to BLUD in Jember Regency, where each Puskesmas has a different background, some being internally strong and others weak, but on the other hand, there are standard requirements that must be achieved as a consequence of the Puskesmas' status change to BLUD, thus requiring strategies from the Puskesmas to achieve this goal. The purpose of this research is to analyze the strategy of UPTD Puskesmas with BLUD status in Jember Regency using the SPACE matrix approach. This research is a descriptive quantitative study. Data processing and analysis were conducted using quantitative analysis, with data collection done cross-sectionally. The sample size of 4 Puskesmas was selected using purposive sampling. Data collection techniques included questionnaires, validated through focus group discussions (FGD), and partly using existing secondary data at the Puskesmas. The analysis of the SPACE matrix shows that Puskesmas with weak internal strength are in the competitive quadrant, while Puskesmas with strong internal strength are in the aggressive quadrant. The organizational effectiveness, measured by aspects of financial performance and service delivery, shows good indicators. These results are influenced by each Puskesmas' strategy, thus requiring the implementation of clear, measurable, and achievable strategies according to an organization's capabilities